THE NECESSITY OF SPEAKING ENGLISH IN HOSPITALITY - Silvi Nabila Zayanti; Evi Rosmiyati; Dewi Kartikasari (Universitas PGRI Palembang, 2023)
This study aimed to explore the speaking proficiency of students in the hospitality field and identify the specific requirements they have for speaking English. The research design employed for this study was qualitative, utilizing a case study approach. To gather data regarding the students' speaking proficiency and their requirements for speaking English in the hospitality field, the researcher employed open-ended questions during data collection with the participants. Thematic analysis, using a coding system, was used to analyze the data and identify patterns related to the students' speaking proficiency and their necessities for speaking English in the hospitality field. The findings of this study revealed that the students' speaking proficiency in the hospitality field served three main purposes: (1) meeting content-related needs, (2) utilizing appropriate learning media, and (3) addressing specific topics. Additionally, the study identified that the necessities of hospitality students in speaking English were focused on facilitating the learning process and optimizing their ability to speak English in the context of the hospitality field.